Surface Plasmon Resonance: Robust Nanostructured Silver and Copper Fabrics with Localized Surface Plasmon Resonance Property for Effective Visible Light Induced Reductive Catalysis (Adv. Mater. Interfaces 6/2016). Issue 6 (March 2016) - Anderson, Samuel R.; Mohammadtaheri, Mahsa; Kumar, Dipesh; O'Mullane, Anthony P.; Field, Matthew R.; Ramanathan, Rajesh; Bansal, Vipul
Abstract : In article number 1500632, V. Bansal, R. Ramanathan and co‐workers develop simple solution‐processable protocols for in situ synthesis of photo‐active fabrics of silver and copper nanoparticles. The hierarchical superstructure of these functional fabrics facilitates the access of reactants and visible light to the catalytically active sites of LSPR‐active nano‐metals. This remarkably improves the efficiency of redox processes under visible light photoexcitation. Mechanistic investigations reveal that light can dramatically influence the electron transfer processes that are critical for efficient redox reactions. The cover image was designed by Ella Maru Studio.